2022
DOI: 10.1186/s12933-022-01618-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of empagliflozin on left ventricular contractility and peak oxygen uptake in subjects with type 2 diabetes without heart disease: results of the EMPA-HEART trial

Abstract: Background The mechanism through which sodium-glucose cotransporter 2 inhibitors (SGLT2i) prevent the incidence of heart failure and/or affect cardiac structure and function remains unclear. Methods The EMPA-HEART trial is aimed at verifying whether empagliflozin improves myocardial contractility (left ventricle global longitudinal strain, LV-GLS) and/or cardiopulmonary fitness (peak oxygen uptake, VO2peak) in subjects with type 2 diabetes (T2D) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…It has been suggested that ketone bodies might have a direct metabolic cardioprotective effect ( 38 ). In patients with T2D without heart disease, treatment with SGLT2 inhibitors increase GLS but only in the group with subclinical myocardial dysfunction (GLS < 16.5%) ( 39 ). This supports the proposed hypothesis that the effect of ketone esters on myocardial contractility depends on the degree of cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that ketone bodies might have a direct metabolic cardioprotective effect ( 38 ). In patients with T2D without heart disease, treatment with SGLT2 inhibitors increase GLS but only in the group with subclinical myocardial dysfunction (GLS < 16.5%) ( 39 ). This supports the proposed hypothesis that the effect of ketone esters on myocardial contractility depends on the degree of cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Breath‐by‐breath minute ventilation, carbon dioxide production (VCO 2 ), and VO 2 were measured using a dedicated cardiopulmonary diagnostic device (Blue Cherry; Geratherm Respiratory GmbH). We defined VO 2peak as the highest median value of the two 30‐s intervals of the last minute of exercise, as previously validated and used 1,21,22 . An automatic procedure determined the anaerobic threshold (AT) based on the V‐slope, ventilatory equivalents and end‐tidal partial pressure methods; AT was verified visually and, if necessary, recalculated 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Cardiac output was calculated as the multiplication of SV and HR. Peripheral extraction, or arteriovenous oxygen difference (Δ(a‐v)O 2 ) was estimated indirectly with a validated approach 1,5,21,22 . Images were acquired concurrently with breath‐by‐breath gas exchange measurements at both baseline and peak of exercise.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations